Effect of Ralgro® implantation periods on masculinity and carcass traits of young bulls and steers. - Gray, D.G.; Corah, L.R.; Unruh, John A.; Dikeman, Michael E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Repeated Ralgro® implantation of young bulls from birth to slaughter resulted in gains and carcass characteristics traits intermediate between non-implanted bulls and steers, and meat palatability traits similar to steers. On the other hand, implanting bulls near birth reduced postweaning gains and both live and carcass masculinity. There is little advantages to implanting bulls from weaning to slaughter without initial implantation at birth.
Keywords: Beef; Implants; Masculinity; Carcass traits; Bulls; Steers